Grassroots Governance?: Chiefs in Africa and the Afro-Caribbean - Ray, Donald Iain; Reddy, P. S. (Purshottama Sivanarian); IASIA (Africa: Missing Voices, 2003)
Traditional leadership is a factor that has long been overlooked in evaluations of rural local government in much of contemporary Sub-Saharan Africa. Grassroots Governance?, an interdisciplinary and intercontinental collection, addresses this gap in African scholarship and brings new perspectives on the integration, or reconciliation, of traditional leadership with democratic systems of local government. Articles from the fields of political science, law, postcolonial studies, anthropology, cultural studies, and policy and administrative studies establish a baseline for best practice in Africa and the Afro-Caribbean while taking into account the importance of traditional leadership to the culture of local governance. Case studies are drawn from Ghana, South Africa, Botswana, Lesotho, and Commonwealth countries in West, East, and Southern Africa, as well as Jamaica.